The genetic diversity and population structure of native horse breeds in Xinjiang, China - Tang, Chi; Yang, Baoyu; Dawulietihan, Gulibaheti; Xue, Li; Liu, Shuyuan; Yalimaimaiti, Yinamujiang; Wang, Qingzheng; Yang, Na; Sun, Xiaoyuan; Wang, Yaru; Wumaier, Ailifeire; Khizat, Serik; et al. (Frontiers in Genetics, 2025)
IntroductionXinjiang is a region renowned for its rich diversity of native horse breeds, making it one of the most affluent equine genetic resource areas in China. While prized for their high adaptability and tolerance to roughage, the conservation of these native breeds faces challenges from the introduction of external breeds and industrial changes. Furthermore, the unknown population structure of Xinjiang horse breeds has hindered effective conservation efforts.MethodsThis study presents the first comprehensive Single Nucleotide Polymorphism (SNP) analysis of seven Xinjiang native horse breeds. We utilized 10X whole-genome sequencing to assess their genetic diversity, population structure, and genetic relationships.ResultsOur findings revealed a high level of population genetic diversity among the Xinjiang native horse breeds. These breeds exhibited significant genetic differentiation from other horse breeds originating from Europe, Central Asia, Western Asia, and other parts of China. Evidence of frequent historical gene flow was detected, particularly among breeds in northern Xinjiang, which were shown to be more closely related to each other.Discussion This study elucidates the distribution patterns, evolutionary characteristics, and substantial genetic diversity of Xinjiang’s native horse breeds. The results provide crucial insights into their unique genetic background and population history. These findings offer valuable theoretical support for establishing core conservation groups of local germplasm, guiding future breeding programs for new cultivars, and further exploration of the characteristics inherent to Xinjiang’s native horse genetic resources.